Atonement - McEwan, Ian 1948- (Cape, 2001)
"On the hottest day of the summer of 1935, thirteen-year-old Briony Tallis sees her sister Cecilia strip off her clothes and plunge into the fountain in the garden of their country house. Watching her is Robbie Turner, her childhood friend who, like Cecilia, has recently come down from Cambridge. By the end of that day the lives of all three will have been changed for ever." --Jacket.